Prevalence and Factors Associated With Low Birth Weight in the Solomon Islands: Evidence From the 2015 Solomon Islands Demographic and Health Survey data - Kaforau, Lydia Sandrah Kuman; Tessema, Gizachew; Jancey, Jonine; Bugoro, H.; Pereira, Gavin (2023)
Low birth weight (LBW) has contributed to more than 80% of under-5 deaths worldwide, most occurring in low- and middle-income countries. We used the 2015 Solomon Islands Demographic and Health Survey data to identify the prevalence and risks associated with LBW in the Solomon Islands. Low birth weight prevalence estimated was 10%. After adjustment for potential confounders, we found the risk of LBW for women with a history of marijuana and kava use was 2.6 times, adjusted relative risk (aRR) 2.64 and 2.5 times (aRR: 2.50) than among unexposed women, respectively. Polygamous relationship, no antenatal care, decision-making by another person were 84% (aRR: 1.84), 73% (aRR: 1.73), and 73% (aRR: 1.73) than among unexposed women, respectively. We also found that 10% and 4% of LBW cases in the Solomon Islands were attributable to a household of more than five members and tobacco and cigarette use history respectively. We concluded that LBW in the Solomon Islands relied more on behavioral risk factors, including substance use as well as health and social risk factors. We recommended further study on kava use and its impact on pregnancy and LBW.